Advanced gear manufacturing and finishing : classical and modern processes - Gupta, Kapil; Jain, Neelesh Kumar; Laubscher, Rudolph (Academic Press is an imprint of Elsevier, 2017)
"Advanced Gear Manufacturing and Finishing offers detailed coverage of advanced manufacturing technologies used in the production of gears, including new methods such as spark erosion machining, abrasive water jet machining, additive layer manufacturing, laser shaping, and sustainable manufacturing of gears."--Page 4 of cover.